2021
DOI: 10.1159/000518654
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in the Severity and Mortality of Neonatal Hypoxic-Ischemic Encephalopathy in the Era of Hypothermia

Abstract: <b><i>Introduction:</i></b> There is a paucity of studies examining temporal trends in the incidence and mortality of moderate-to-severe hypoxic-ischemic encephalopathy (HIE) during the last decade of therapeutic hypothermia (TH). <b><i>Methods:</i></b> Multicenter cross-sectional study of all infants ≥35 weeks gestational age diagnosed with moderate-to-severe HIE within 6 h of birth in an extensive region of Spain between 2011 and 2019, in order to detect trend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
8
1
1
Order By: Relevance
“…The observed fall in the proportion of severe birth asphyxia deaths could relate to changes in treatment. A large multi‐centre Spanish study observed a slight decline in mortality from hypoxic‐ischaemic encephalopathy mortality from 2011 to 2019 associated with the use of therapeutic hypothermia 30 . However, the observed change in our study may be more linked to changes in admission patterns.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The observed fall in the proportion of severe birth asphyxia deaths could relate to changes in treatment. A large multi‐centre Spanish study observed a slight decline in mortality from hypoxic‐ischaemic encephalopathy mortality from 2011 to 2019 associated with the use of therapeutic hypothermia 30 . However, the observed change in our study may be more linked to changes in admission patterns.…”
Section: Discussioncontrasting
confidence: 52%
“…A large multi‐centre Spanish study observed a slight decline in mortality from hypoxic‐ischaemic encephalopathy mortality from 2011 to 2019 associated with the use of therapeutic hypothermia. 30 However, the observed change in our study may be more linked to changes in admission patterns. Infants with HIE in Victoria are usually managed in perinatal centres, with our centre increasingly focused on specialised complex surgical and medical conditions.…”
Section: Discussionmentioning
confidence: 56%
“…Hypoxic-ischemic encephalopathy (HIE) is a neurologic condition that results from brain injury in neonates due to perinatal conditions such as pre-eclampsia and birth asphyxia. HIE is estimated to occur in 1–8 per 1000 births and is one of the leading causes of morbidity and mortality in infants worldwide [ 1 , 2 ]. At present, there are very limited therapeutic options available besides hypothermia [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal hypoxic-ischemic brain damage (HIBD), which is caused by perinatal asphyxia, is a primary etiology for acute neonatal mortality and long-term infant neurological dysfunction (1)(2)(3). The incidence of neonatal HIBD is 1-3 per 1,000 in developed countries, while in developing countries the rate can be as high as 25 per 1,000 (4,5).…”
Section: Introductionmentioning
confidence: 99%